2006
DOI: 10.1124/jpet.105.098970
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial Targeting of High-Affinity Multivalent Polymer Nanocarriers Directed to Intercellular Adhesion Molecule 1

Abstract: Targeting of diagnostic and therapeutic agents to endothelial cells (ECs) provides an avenue to improve treatment of many maladies. For example, intercellular adhesion molecule 1 (ICAM-1), a constitutive endothelial cell adhesion molecule upregulated in many diseases, is a good determinant for endothelial targeting of therapeutic enzymes and polymer nanocarriers (PNCs) conjugated with anti-ICAM (anti-ICAM/PNCs). However, intrinsic and extrinsic factors that control targeting of anti-ICAM/PNCs to ECs (e.g., ant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

27
278
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
1
1

Relationship

5
4

Authors

Journals

citations
Cited by 178 publications
(305 citation statements)
references
References 39 publications
27
278
0
Order By: Relevance
“…We tested distribution of the radiolabeled TM antibodies and GOX conjugates one hour after IV injection. Previous studies of immunotargeting of radiolabeled conjugates directed to highly accessible endothelial determinants such as TM, angiotensin-converting enzyme (ACE), PECAM-1, intercellular adhesion molecule 1 (ICAM-1) and GP90 showed that their maximum uptake in the lungs occurs within 15-30 min, followed by a short 15-30 min stable period and subsequent reduction of the pulmonary level observed at times more than one hour after IV injection [22,25,27,[46][47][48][49][50][51][52]. Therefore, the kinetics of lung edema development showing a maximum 4 hour after injection of a lower dose of the conjugate selected to avoid overt early lethality (Fig.4C) is not due to delayed accumulation of GOX in the lungs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We tested distribution of the radiolabeled TM antibodies and GOX conjugates one hour after IV injection. Previous studies of immunotargeting of radiolabeled conjugates directed to highly accessible endothelial determinants such as TM, angiotensin-converting enzyme (ACE), PECAM-1, intercellular adhesion molecule 1 (ICAM-1) and GP90 showed that their maximum uptake in the lungs occurs within 15-30 min, followed by a short 15-30 min stable period and subsequent reduction of the pulmonary level observed at times more than one hour after IV injection [22,25,27,[46][47][48][49][50][51][52]. Therefore, the kinetics of lung edema development showing a maximum 4 hour after injection of a lower dose of the conjugate selected to avoid overt early lethality (Fig.4C) is not due to delayed accumulation of GOX in the lungs.…”
Section: Discussionmentioning
confidence: 99%
“…Solid poly(lactic-co-glycolic acid) PLGA nanoparticles were prepared by a modified single emulsion technique, as described before [27]. Similar to solvent extraction of microsphere particle preparations reviewed by Freitas et al [28] and other nanoparticle formulations [29] this nanoprecipitation method involves dissolving PLGA in a water miscible solvent, such as acetone, and addition to a stabilizing surfactant solution.…”
Section: Conjugation Of Glucose Oxidase To Anti-tm and Polymer Beadsmentioning
confidence: 99%
“…To determine whether shape-enhanced endothelial accumulation is also observed under physiological conditions, nanospheres and nanorods coated with ICAM-mAb (YN1/1.7.4) or nonspecific mouse IgG were injected intravascularly into healthy mice. Under healthy conditions, ICAM-1 is expressed at basal levels in the endothelium of the lungs (31,32) and has been used extensively for nanoparticle targeting to the lungs (33). ICAM-mAb-coated spheres and rods exhibited higher accumulation in the lungs compared with their IgG-coated counterparts.…”
Section: Shear-dependent Adhesion Of Nanoparticles In Synthetic Micromentioning
confidence: 99%
“…Whether it is due to targeting via positively-charged moieties or by specific affinity means, targeted delivery of drug carriers offers advantages over direct targeting of therapeutics. Apart from the described advantages posed by increased solubility, circulation time, and release control, carriers bearing multiple copies of an affinity moiety display greater affinity due to this multivalency, compared to drugs that are directly coupled to one copy of the same affinity molecule (Muro, et al, 2006a). As described below, multivalency of targeted carriers also provides tight binding to cell surface receptors, which can favor uptake within the cell, a necessary requirement for many diagnostic and therapeutic applications.…”
Section: Targetingmentioning
confidence: 99%